Antimicrobial Activity of Polyoxometalate Ionic Liquids against Clinically Relevant Pathogens. Issue 6 (13th June 2017) - Kubo, Anna‐Liisa; Kremer, Lea; Herrmann, Sven; Mitchell, Scott G.; Bondarenko, Olesja M.; Kahru, Anne; Streb, Carsten
Abstract: The activity of a new class of antimicrobials—polyoxometalate ionic liquids (POM‐ILs)—is systematically investigated. The prototype POM‐ILs feature Keggin‐type anions (α‐SiW11 O39 8− ) and tetraalkylammonium ions as active cationic species. Antimicrobial tests of the POM‐ILs against important human pathogens show that variation of the alkyl chain length of the cation leads to significant changes in antimicrobial activity against the medically relevant Gram‐negative bacteria Escherichia coli and Pseudomonas aeruginosa, and especially against the Gram‐positive Staphylococcus aureus . Owing to the unique materials properties of the POM‐ILs, such as high viscosity and water immiscibility, applications of antimicrobial surface coatings against airborne pathogens or for water decontamination can be envisaged. Furthermore, the combination of antimicrobially active cations with POM anions might afford new POM‐ILs with two active components. Abstract : Positive about the future : The antimicrobial activities of three prototype polyoxometalate ionic liquids (POM‐ILs) against the clinically important bacterial strains Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa were examined (see figure). The highest activity to date for POM‐based antimicrobials is reported. Variation of the tetraalkylammonium cation is shown to be the decisive factor for antimicrobial activity, so that novel high‐performance POM‐ILs for surface coatings or water filters can now be designed.